A practical framework for engaging water champions in the One Health approach: lessons from the Akaki Catchment, Ethiopia - Beza, Habtamu Mulat; Haile, Alemseged Tamiru; Kibret, M.; Nigussie, Likimyelesh; Yibel, B.; Haile, L.; Kifle, M.; Mateo-Sagasta, Javier (International Water Management Institute, 2025)
Water’s role in the spread of antimicrobial resistance (AMR) has been underrepresented in Ethiopia's One Health (OH) approach. To address this gap, the International Water Management Institute (IWMI) co-developed, alongside Water Champions (WCs), an approach to include water in national and regional OH strategies and tested it in the Akaki watershed. The approach to identifying and engaging WCs in OH included defining their roles, analyzing the engagement process, finding challenges and opportunities, and enhancing cross-sectoral collaboration. Instead of imposing a predesigned framework for the engagement of WCs, we developed a systematic framework by documenting and synthesizing the activities, achievements, and experiences of WCs in the Akaki catchment. This report presents a framework for engaging WCs in Ethiopia’s OH approach, drawing lessons from the Akaki watershed. The framework was co-developed by IWMI and partners to integrate the water sector into national OH strategies, recognizing water’s underrepresented role in the emergence and spread of AMR. The engagement process is designed to be flexible and evidence-based, aiming to identify and empower WCs across health, environmental, and water sectors. Key components of the framework include stakeholder analysis, Terms of Reference (ToR) development, capacity building, advocacy, and monitoring, all structured to enhance cross-sectoral cooperation and awareness. The process was carried out in three phases. The initial phase identified key water issues aligned with the OH approach. The subsequent two phases focused on securing stakeholder commitment and collaboratively developing and reviewing the adaptive framework for engaging WCs. Data for framework development was gathered through key informant interviews, observations during regular meetings, awareness-raising activities, and reviews of relevant documents. The structured phases of the framework effectively enhanced cross-sectoral cooperation and awareness. However, challenges remain, including limited institutional support, lack of dedicated funding, and the perception of WC roles as secondary duties. The report concludes that formalizing WC roles within OH governance and strengthening intersectoral collaboration, capacity building, and performance monitoring are essential for sustainability. The Akaki experience demonstrates that integrating WCs into the OH approach can significantly advance AMR prevention and promote holistic water-health management. Overall, embedding WCs within Ethiopia’s OH approach represents a major step toward recognizing water as a vital element in addressing interconnected human, animal, and environmental health challenges.